Crafting electricity through social protest: afro-descendant and indigenous Embera communities protesting for hydroelectric infrastructure in Utría National Park, Colombia (2019)
Development infrastructure is often discussed in terms of opposition by local and indigenous communities. Based on ethnographic fieldwork, we present the case of local indigenous Embera and Afro-descendant communities in Chocó, Colombia, that protested first to gain, and later to maintain access to electricity produced by the Mutatá hydroelectric dam in Utría National Park. In the context of development politics, taking into account the revised Colombian Constitution of 1991, we explore the motivations and expectations that underpinned these two protests. We contextualize the Afro-descendant community’s protests for development as a continuation of the Afro-descendant peoples’ struggle for social and political participation. We argue, on the other hand, that the Embera’s participation implies both an act of solidarity with their Afro-descendant kin and a performance of what Herbert Marcuse has called Refusal, in the context of late-industrial society. We use this case to help address potentially overlooked subtleties in the representation of the postcolonial subject in development politics, showing how long-term historical structures, reaching back to Spanish colonialization, continue to permeate and shape the desired futures in both communities as well as the ways in which they engage with and reject the contemporary Colombian state’s project of development.